Priming healthcare students on the importance of non-technical skills in healthcare: How to set up a medical escape room game experience. (2nd November 2019) - Rosenkrantz, Oscar; Jensen, Theo Walther; Sarmasoglu, Senay; Madsen, Sophie; Eberhard, Kristine; Ersbøll, Annette Kjaer; Dieckmann, Peter
Abstract: Background: Non-technical skills (NTS) are essential for healthcare professionals. Earlier the students are made aware of this, the more time they have to acquire these skills. Escape rooms have been introduced in the medical literature but a detailed published manual on setting up and running such a learning modality is lacking. The purpose of this paper is to describe the use of an escape room to create learning opportunities, including detailed instructions, as well as an evaluation from two settings. Methods: A medical escape room focusing on NTS was developed and run in two different settings: a university summer school – EMSS17, and an international healthcare congress – EMS2018. Questionnaire data investigating entertainment value, self-evaluated use of NTS and ideas for further use of the escape room concept was obtained. Further, video analyses were conducted to triangulate self-rated analyses. Results: Majority of the participants found the escape room psychologically safe and enjoyable and would recommend the concept to other students and healthcare professionals. Video analyses showed the same tendencies regarding the use of NTS as reported by participants. Conclusions: This paper presents a fully applicable escape room manual, ready to implement, adapt, and modify. Evaluation data support the proof of concept.